A potent antimicrobial compound isolated from Clathria cervicornis. Issue 1 (1st January 2015) - Sun, Xiuxiu; Sun, Shi; Ference, Christopher; Zhu, Wenjun; Zhou, Ninghui; Zhang, Yifan; Zhou, Kequan
Graphical abstract: A potent antimicrobial compound, crambescidin 800, was isolated from Clathria cervicornis . Abstract: The sponge of Clathria cervicornis is commonly used in traditional medicine. This study aims to identify the active compound in C. cervicornis and to evaluate its antimicrobial activity. The purified active compound was determined to be crambescidin 800 and was found to be highly active against Acinetobacter baumannii (minimal inhibitory concentration, MIC = 2 μg/ml), Klebsiella pneumoniae (MIC = 1 μg/ml) and Pseudomonas aeruginosa (MIC = 1 μg/ml). A potent antimicrobial compound, crambescidin 800, was isolated in Clathria cervicornis . It is extremely active against three common pathogenic bacteria.